2023
DOI: 10.1038/s41467-023-38056-w
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-driven multifunctional peptide engineering for sustained ocular drug delivery

Abstract: Sustained drug delivery strategies have many potential benefits for treating a range of diseases, particularly chronic diseases that require treatment for years. For many chronic ocular diseases, patient adherence to eye drop dosing regimens and the need for frequent intraocular injections are significant barriers to effective disease management. Here, we utilize peptide engineering to impart melanin binding properties to peptide-drug conjugates to act as a sustained-release depot in the eye. We develop a supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Specifically, they demonstrated that brimonidine, an alpha-agonist used for the treatment of chronic glaucoma, conjugated with an engineered peptide HR97 (FSGKRRKRKPR) improved, by ≈17 fold, the cumulative IOP-lowering effect compared to free injection over a period of 20 days. [66] Although melanin binding is promising for maintaining therapeutic levels for a prolonged period, the inherent variability in melanin levels in individuals poses a challenge. [64,67] Melanin content in ocular cells can differ significantly among individuals due to factors such as genetic background, age, and ethnicity: individuals with brown eyes have much more melanin within their iris than those with blue eyes.…”
Section: Greater Ocular Cell Targeting Fewer Off-target Side Effectsmentioning
confidence: 99%
“…Specifically, they demonstrated that brimonidine, an alpha-agonist used for the treatment of chronic glaucoma, conjugated with an engineered peptide HR97 (FSGKRRKRKPR) improved, by ≈17 fold, the cumulative IOP-lowering effect compared to free injection over a period of 20 days. [66] Although melanin binding is promising for maintaining therapeutic levels for a prolonged period, the inherent variability in melanin levels in individuals poses a challenge. [64,67] Melanin content in ocular cells can differ significantly among individuals due to factors such as genetic background, age, and ethnicity: individuals with brown eyes have much more melanin within their iris than those with blue eyes.…”
Section: Greater Ocular Cell Targeting Fewer Off-target Side Effectsmentioning
confidence: 99%
“…As a data-driven methodology, its outcomes would be impaired by the limited number of available studies or inconsistent data sets resulting from experimental variations. 9,10 Additionally, different peptides may possess distinct working mechanisms that are not directly incorporated into existing peptide databases, further impacting the efficacy of machine learning algorithms. 16 In fact, in nearly all machine-learning scenarios, peptides with higher predicted scores may exhibit poorer biological activity in actual tests.…”
Section: Introductionmentioning
confidence: 99%
“…16 In fact, in nearly all machine-learning scenarios, peptides with higher predicted scores may exhibit poorer biological activity in actual tests. [7][8][9][10]15,17 On the other hand, human expertise has been proven helpful in improving peptide performance despite potential biases present within it. 8,18−20 Therefore, effectively leveraging the advantages of machine learning to augment human knowledge holds greater promise for advancing peptide-based drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning techniques possess numerous usages in the manufacturing of filters, soft tissue prosthetics, tissue engineering scaffolds, reinforced composites, porous electrodes for battery separators, protective garments, and controlled drug delivery 6 . Indeed, the science of drug delivery systems (DDS) has dramatically developed in recent years, especially by using electrospinning techniques 7 , 8 . It is worth mentioning that one of the advantages of these techniques is the production of highly porous fibers, which increases their surface-to-volume ratio and can improve drug loading 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the science of drug delivery systems (DDS) has dramatically developed in recent years, especially by using electrospinning techniques 7 , 8 . It is worth mentioning that one of the advantages of these techniques is the production of highly porous fibers, which increases their surface-to-volume ratio and can improve drug loading 7 , 8 . In addition to the high surface-to-volume ratio of fibers, unlike other techniques, such as encapsulation by using the electrospinning technique in DDS designing, therapeutic compounds can be conveniently embedded within polymeric carriers 9 .…”
Section: Introductionmentioning
confidence: 99%